Journey Camino de Santiago : Camino Francés - Eveleigh, Mark; Kaminski, Anna (Lonely Planet, 2025)
Lonely Planet's Journey Camino de Santiago: the Camino Frances is the definitive guide to one of the world's great adventures - bringing you closer to the culture, history and landscapes you'll encounter along the way. Get inspiration, ideas and planning tips from our experts who have walked every step to uncover unique experiences you can make all your own. Have the best Spanish omelette you'll ever eat in Valdelafuente, wake to monks chanting at dawn in Roncesvalles, and order a nightcap of patxaran before you leave Navarra.